The construction of functional protein nanotubes by small molecule-induced self-assembly of cricoid proteins. Issue 21 (22nd February 2016) - Miao, Lu; Fan, Qiusheng; Zhao, Linlu; Qiao, Qinglong; Zhang, Xiyu; Hou, Chunxi; Xu, Jiayun; Luo, Quan; Liu, Junqiu
Abstract : Induced by small molecular ethylenediamine and "zero-length" covalent crosslinking, covalently crosslinked SeSP1 protein nanotubes with great GPx activity was fabricated. Abstract : A simple strategy has been developed to construct high-ordered protein nanotubes using electrostatic interactions and "zero-length" crosslinking induced by small molecular ethylenediamine. Furthermore, utilizing covalent crosslinking, we constructed stable nanoenzymes with multi-glutathione peroxidase (GPx) active centers on the surface of the nanotubes, which were anticipated to be ideal functional bionanomaterials.